IL-26, a Cytokine With Roles in Extracellular DNA-Induced Inflammation and Microbial Defense - Larochette, Vincent; Miot, Charline; Poli, Caroline; Beaumont, Elodie; Roingeard, Philippe; Fickenscher, Helmut; Jeannin, Pascale; Delneste, Yves (Frontiers in Immunology, 2019)
Interleukin 26 (IL-26) is the most recently identified member of the IL-20 cytokine subfamily, and is a novel mediator of inflammation overexpressed in activated or transformed T cells. Novel properties have recently been assigned to IL-26, owing to its non-conventional cationic and amphipathic features. IL-26 binds to DNA released from damaged cells and, as a carrier molecule for extracellular DNA, links DNA to inflammation. This observation suggests that IL-26 may act both as a driver and an effector of inflammation, leading to the establishment of a deleterious amplification loop and, ultimately, sustained inflammation. Thus, IL-26 emerges as an important mediator in local immunity/inflammation. The dysregulated expression and extracellular DNA carrier capacity of IL-26 may have profound consequences for the chronicity of inflammation. IL-26 also exhibits direct antimicrobial properties. This review summarizes recent advances on the biology of IL-26 and discusses its roles as a novel kinocidin.